2021
DOI: 10.1111/1541-4337.12871
|View full text |Cite
|
Sign up to set email alerts
|

Water holding properties of Atlantic salmon

Abstract: With global seafood production increasing to feed the rising population, there is a need to produce fish and fishery products of high quality and freshness. Water holding properties, including drip loss (DL) and water holding capacity (WHC), are important parameters in determining fish quality as they affect functional properties of muscles such as juiciness and texture. This review focuses on the water holding properties of Atlantic salmon and evaluates the methods used to measure them. The pre‐ and postmorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…The moisture content and water‐holding capacity of aquatic products affect their nutrients, tenderness, colour, taste and other qualities, and are important parameters for evaluating the quality of aquatic products (Chan et al ., 2022). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The moisture content and water‐holding capacity of aquatic products affect their nutrients, tenderness, colour, taste and other qualities, and are important parameters for evaluating the quality of aquatic products (Chan et al ., 2022). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The WHC of fish products is an important quality parameter since it represents the capacity of flesh to retain its internal water [34]. The WHC values increased from 77.25% in the raw tuna samples to 97.29% in the final product.…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…For rainbow trout, the gel-breaking stress, breaking strain, and gel strength decreased slightly at three storage temperatures when the muscles started to unstiffen. This phenomenon can be attributed to the severe rigidity bonding between the myofibers and the weakening of muscle tissue during storage (Chan et al, 2022). Notably, HVEF treatment avoided degradation of proteins (myosin and actin) in the filets (Xie et al, 2021), and Qian et al (2022) reported that treatment with 10 and 15 kV/m slowed the deterioration of texture properties (hardness and elasticity) during refrigeration, presumably related to protease activity inhibition.…”
Section: Gel Strength Propertiesmentioning
confidence: 99%